Out of the Smokescreen: does an anti-smoking advertisement affect young women's perception of smoking in movies and their intention to smoke?. Issue 3 (25th August 2004) - Edwards, C A; Harris, W C; Cook, D R; Bedford, K F; Zuo, Y
Abstract : Objective: To evaluate the effect of an anti-smoking advertisement on young women's perceptions of smoking in movies and their intention to smoke. Subjects/setting: 2038 females aged 12–17 years attending cinemas in New South Wales, Australia. Design/intervention: Quasi-experimental study of patrons, who were surveyed after having viewed a movie at their local cinema. The control group was surveyed during week 1 and the intervention group, during week 2. Before seeing the movie in week 2, a 30 second anti-smoking advertisement was shown, which featured a well known female actor drawing attention to the prevalence of smoking in movies. Outcomes: Attitude of current smokers and non-smokers to smoking in the movies; intention of current smokers and non-smokers to be smoking in 12 months time. Results: Among non-smokers, 48.2% of the intervention subjects thought that the smoking in the movie they viewed was "not OK" compared with 28.3% of the control subjects (p < 0.0001). However, there was no difference among smokers in the intervention (26.4%) and control (16.9%) groups (p = 0.28). A higher percentage of current smokers in the intervention group indicated they were unlikely to smoke in 12 months time (47.8%) than smokers in the control condition (31.9%) (p = 0.03). For non-smokers, there was no difference in smoking intentions between conditions, with 95% saying they would be unlikely to be smoking in 12 months time. Conclusions: This "real world" study suggests that placing an anti-smoking advertisement before movies containing smoking scenes can help to "immunise" young women against the influences of film stars smoking.